Relationship of Emotional Intelligence from the Diversity Perspective in Project Outcomes in Technology Projects (Global Journal of Management and Business Research, 2016)
The purpose of the quantitative correlational research study was to examine if a significant relationship existed between the Emotional Intelligence (EI) competencies of Hispanic team members and project outcomes within the technology sector in the United States. Therefore the objective was to explore the degree of association or relationship between the identified predictor and criterion variables. The predictor variables included the EI competencies: Emotional Self-Awareness(ESA), Emotional Self-Management(ESM), Emotional Awareness of Others(EAO), Emotional Management of Others(EMO), and the criterion variables: Project Timeliness(PT), In-Budget Project(PB), and Scope Creep(SC).
Keywords: emotional intelligence; emotional; intelligence; hispanics; diversity; project outcomes; ei; ei competencies; technology; quantitative; correlational